An economic analysis of silvicultural options for broadleaved woodland (volume I) - Pryor, S; Peterken, G (Commenwealth Forestry Institute, University of Oxford, 1982)
The purpose of this study is to compile for the Nature Conservancy Council information on the profitability of the silvicultural options available in three types of broadleaved woodland: Acid Western Oak, Oak-Ash, and Oak standards over Hazel coppice. The Nee specified that the economic analyses should relate to actual woods, chosen as representative examples of each of the woodland types, with the intention that these results could then be applied to other woodlands of the same type. There are two major problems associated with this study. Firstly, there is a very large variation in woodlands, even within a given type; the options that are appropriate to a 'representative example' may well not be profitable, or even applicable to other woods of the same type. This is due not only to the great differences in the stand characteristics but also to the wide ,variation in the many other factors that affect the suitability and profitability of a silvicultural option. Secondly, when predicting productivity and profitability,estimates of the levels of many variables must be made, and such estimates are bound to be, to some extent, subjective; this is especially true in forestry where there are very few published estimates of such variables as establishment costs and timber prices. In an attempt to overcome the site-specificity and subjectivity of the results, and thus make them more generally applicable, the economic analyses have been carried out in such a way as to retain most of the parameters that determine profitability as variables. Thus not only can the subjective estimates that were used be altered, and sensitivity analyses carried out, but the results can also be readily adapted so that they apply to other woods, where conditions are different...